INOVASI PENGELOLAAN LIMBAH DOMESTIK MENJADI KOMPOS KUALITAS PRIMA - Tia Rostaman; Etty Riani; Sugeng A. Putranto (EnviroScienteae, 2023)
A large amount of domestic waste is unfortunately not matched by proper management. Like leaf waste, there is also vegetable waste in traditional markets, which is disposed of in open dumping without further management. The overflow of garbage will certainly leave environmental disturbances and bad smells. Research on the processing of domestic solid waste using a composter is generally only carried out in one stage, so the results of cutting domestic waste from the composter are still rough. In addition, bacteria administration is usually done at the end, so it is less effective in terms of time and cost. This study aims to design compost production innovations that meet SNI standards. The research was conducted by comparing the two main raw materials for the compost, namely vegetables and leaves. Based on the research results, it was found that the compost produced was able to produce fertilizer with the nutrients N, C/P, P, K, and C/N following SNI 7763: 2018. Compost with the best results is compost with leaves as the main raw material.